RANCANG BANGUN SISTEM INFORMASI PENJUALAN MEMANFAATKAN PLUG IN WOOCOMMERCE DAN METODE SEO - Marlina; Yafet Yapari; Ahyar Muawwal (STMIK KHARISMA Makassar, 2021)
This researcher aims to design an online-based e-commerce sales information system and by using Woocommerce SEO techniques so that when a particular search is performed, this e-commerce page is on the front page of the search engines. SEO is a series of systematic processes that aim to increase the volume and quality of traffic from search engines to specific website addresses by utilizing the natural working mechanism of the algorithm from the search engines. After the author applies it in e-commerce that the author designs and builds, then at the time of the search, it occupies a position on the first page, so the author concludes that the research was successful.